The mechanism of international cooperation accordingly to UN Convention against Transnational Organized Crime //El mecanismo de cooperación internacional de acuerdo con la Convención de la ONU contra la Delincuencia Organizada Transnacional - Romashkin, Snizhana; Shulzhenko, Nadiia; Liubov, Kotova (Revista de la Universidad del Zulia, 2020)
Abstract The article considers the mechanisms for fighting transnational crime and international cooperation in accordance with the United Nations Convention against Transnational Organized Crime and identifies the main factors that complicate international cooperation processes to combat transnational crime. The authors emphasize that international cooperation in the fight against crime is key to the success and guarantee of international security. The main objectives of the article are to carry out a comprehensive analysis of the concept of "organized crime" in accordance with the United Nations Convention against Transnational Organized Crime, to determine the corpus delicti, as well as to improve International Law to combat transnational crime. In the article the following methods are used: induction, deduction, analogy, as well as historical, dialectical, formal-legal methods. The article provides us with the complex results related to the key mechanisms of international cooperation according to the United Nations Convention against Transnational Organized Crime. Resumen El artículo considera los mecanismos de lucha contra la delincuencia transnacional y la cooperación internacional de acuerdo con la Convención de las Naciones Unidas contra la Delincuencia Organizada Transnacional e identifica los principales factores que complican los procesos de cooperación internacional para combatir la delincuencia transnacional. Los autores enfatizan que la cooperación internacional en la lucha contra el crimen es clave en el éxito y garantía de la seguridad internacional. Los principales objetivos del artículo consisten en un análisis integral del concepto de "delincuencia organizada" de acuerdo con la Convención de las Naciones Unidas contra la Delincuencia Organizada Transnacional, para determinar el corpus delicti, así como mejorar el Derecho Internacional para combatir la delincuencia transnacional. En el artículo se utilizan los siguientes métodos: inducción, deducción, analogía, así como métodos históricos, dialécticos, formales-legales. El artículo nos proporciona los resultados complejos relacionados con los mecanismos clave de cooperación internacional de acuerdo con la Convención de las Naciones Unidas contra la Delincuencia Organizada Transnacional.